Catalyst, method for producing a catalyst, film, and film electrode assembly

JP2026166620APending Publication Date: 2026-10-14NAT UNIV CORP TOKAI NAT HIGHER EDUCATION & RES SYST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2025059676
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0012】 本開示によれば、優れた特性を有する触媒を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026166620000001_ABST
    Figure 2026166620000001_ABST
Patent Text Reader

Abstract

To provide a catalyst with excellent properties. [Solution] The catalyst 1 comprises catalyst particles 2, each containing a shell 4 containing a carbon material and a core 5 containing a metal material enclosed within the shell 4, and a carrier 3 supporting the catalyst particles 2. The shell 4 contains amorphous carbon doped with heteroatoms. The carrier 3 contains carbon nanotubes.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to a catalyst, a method for producing the catalyst, a film, and a film electrode assembly. [Background technology]

[0002] Fuel cells are becoming widely used. In particular, polymer electrolyte fuel cells (PEFCs) are expected to become widespread in fields such as portable devices, home cogeneration, and fuel cell vehicles because they can operate at room temperature and can be made small and lightweight. [Prior art documents] [Patent Documents]

[0003] [Patent Document 1] Japanese Patent Publication [Overview of the Initiative] [Problems that the invention aims to solve]

[0004] When hydrogen is used as fuel in PEFCs, platinum is primarily used as a catalyst. Because platinum is expensive, technologies to reduce its usage are needed. Furthermore, technologies to improve the durability of the catalyst are also required.

[0005] This disclosure is made in view of these challenges, and its purpose is to provide a catalyst having excellent properties. [Means for solving the problem]

[0006] To solve the above problems, a catalyst according to one aspect of the present disclosure comprises catalyst particles including a shell containing a carbon material, a core containing a metallic material encapsulated within the shell, and a support for supporting the catalyst particles. The shell contains heteroatom-doped amorphous carbon. The support contains carbon nanotubes.

[0007] Another aspect of the present disclosure is a manufacturing method. This method includes the steps of: preparing a mixed solution containing a compound containing heteroelements and carbon nanotubes; heating carbon nanotubes removed from the mixed solution to thermally decompose the compound and thereby incorporate heteroelements into the carbon nanotubes; applying a voltage from an electrode containing a metallic material to generate a plasma in a solution containing carbon nanotubes containing heteroelements; and supporting catalyst particles, which are particles of the metallic material synthesized by the solution plasma and coated with heteroelement-doped amorphous carbon, onto carbon nanotubes.

[0008] Another aspect of the present disclosure is also a manufacturing method. This method includes the steps of: generating a plasma in a solution containing a compound containing a heteroelement; adding carbon nanotubes to the solution to support heteroelement-doped amorphous carbon on the carbon nanotubes; and heating a solution containing the heteroelement-doped amorphous carbon-supported carbon nanotubes and a metallic material to support catalyst particles, in which particles of the metallic material are coated with heteroelement-doped amorphous carbon, on the carbon nanotubes.

[0009] Another aspect of the present disclosure is also a manufacturing method. This method includes the steps of: preparing a solution containing a compound containing a heteroelement, a metallic compound containing a metallic material, and carbon nanotubes; generating a plasma in the solution; heating carbon nanotubes removed from the solution; and supporting catalyst particles, which are particles of the metallic material synthesized by the solution plasma coated with heteroelement-doped amorphous carbon, onto the carbon nanotubes.

[0010] Another aspect of this disclosure is a film, which comprises one of the catalysts described above.

[0011] A further aspect of the present disclosure is a membrane electrode assembly, which comprises the above-mentioned membrane and an electrolyte membrane. [Effects of the Invention]

[0012] According to this disclosure, it is possible to provide a catalyst having excellent properties. [Brief explanation of the drawing]

[0013] [Figure 1] This figure schematically shows a catalyst according to an embodiment of the present disclosure. [Figure 2] This flowchart shows the steps of a first method for producing a catalyst according to an embodiment of the present disclosure. [Figure 3] This flowchart shows the steps of a second method for producing a catalyst according to an embodiment of the present disclosure. [Figure 4] This flowchart shows the steps of a third method for producing a catalyst according to an embodiment of the present disclosure. [Figure 5] This figure shows the structure of the catalyst in Example 1. [Figure 6] This figure shows the chemical composition of the catalyst in Example 1. [Figure 7] This figure shows the results of the electrochemical measurement of the catalyst in Example 1. [Figure 8] This figure shows the results of the durability test of the catalyst in Example 1. [Figure 9] This figure shows the results of the durability test of the catalyst in Example 1. [Figure 10] This figure shows the results of the durability test of the catalyst in Example 1. [Figure 11] This figure shows the results of the durability test of the catalyst in Example 1. [Figure 12] This figure shows the results of the durability test of the catalyst in Example 1. [Figure 13] This figure shows the structure of the catalyst in Example 2. [Figure 14] This figure shows the results of the electrochemical measurement of the catalyst in Example 2. [Figure 15] This figure shows the results of the durability test of the catalyst in Example 2. [Figure 16] This figure shows the results of the durability test of the catalyst in Example 2. [Figure 17] This figure shows the results of the durability test of the catalyst in Example 2. [Figure 18] This figure shows the results of the durability test of the catalyst in Example 2. [Figure 19] This figure shows the results of the durability test of the catalyst in Example 2. [Figure 20] This figure shows the results of the durability test of the catalyst in Example 2. [Figure 21] This figure shows the manufacturing conditions for the catalyst of Example 3. [Figure 22] This figure shows the structure of the catalyst in Example 3. [Figure 23] This figure shows the structure of the catalyst in Example 3. [Figure 24] This figure shows the chemical composition of the catalyst in Example 3. [Figure 25] This figure shows the results of the electrochemical measurement of the catalyst in Example 3. [Figure 26] This figure shows the results of the electrochemical measurement of the catalyst in Example 3. [Figure 27] This figure shows the platinum loading amount, ECSA, MA, and SA of the catalyst in Example 3. [Modes for carrying out the invention]

[0014] Figure 1 schematically shows a catalyst according to an embodiment of the present disclosure. Catalyst 1 is mainly used to promote the oxygen reduction reaction (ORR) in a fuel cell.

[0015] Catalyst 1 comprises catalyst nanoparticles 2 and a carrier 3 that supports the catalyst nanoparticles 2.

[0016] The catalyst nanoparticle 2 comprises a shell 4 containing a carbon material and a core 5 encapsulated within the shell 4. The core 5 contains a metallic material having catalytic function. The metallic material may be platinum (Pt), palladium (Pd), or an alloy containing at least one of these. The shell 4 contains a carbon material mainly composed of carbon. The shell 4 may also contain amorphous carbon. The shell 4 may also contain one to several layers of graphene. The catalytic activity can be improved by the interaction between the carbon material constituting the shell 4 and the metallic material constituting the core 5, thereby reducing the amount of precious metals such as platinum that can be supported, and thus reducing the manufacturing cost of the catalyst 1. Furthermore, by covering the core 5 with the shell 4, the elution and loss of the metallic material constituting the core 5 and the progression of Ostwald aging can be suppressed, thereby improving the durability of the catalyst 1. In addition, the generation of hydrogen peroxide and poisoning of the catalyst can be suppressed, thereby improving the performance and durability of the catalyst 1. Furthermore, oxygen adsorption can be promoted, thus accelerating the oxygen reduction reaction.

[0017] Shell 4 contains heteroelements. Heteroelements may be Group 15 elements such as nitrogen (N) and phosphorus (P), or Group 16 elements such as sulfur (S). Heteroelements may substitute for carbon atoms constituting Shell 4, or they may be chemically or physically bonded to carbon atoms constituting Shell 4. Heteroelements doped into the carbon material can reduce metal ions contained in the metal material to elemental metals, thereby improving the catalytic activity of the metal material. Furthermore, heteroelements doped into the carbon material can impart asymmetric spin and charge density to the bands of the carbon material, increasing the electronic interaction between the heteroelements and the metal particles of Core 5 and their spatial confinement effect, thereby enhancing the catalytic activity and stability of catalyst nanoparticles 2.

[0018] The support 3 contains carbon nanotubes. This improves the oxidation resistance of the support 3 even in the high-temperature and high-potential environment when the fuel cell is in operation, thereby improving the durability of the support 3. It also improves the electrical and thermal conductivity of the catalyst layer. Furthermore, it increases the proportion of voids 6 in the catalyst layer, improving gas diffusion and suppressing concentration polarization at the output point.

[0019] The support 3 may contain single-walled carbon nanotubes. Single-walled carbon nanotubes generally have higher crystallinity than multi-walled carbon nanotubes, and therefore exhibit superior oxidation resistance in high-temperature, high-potential environments. The single-walled carbon nanotubes may be synthesized by the enhanced Direct Injection Pyrolytic Synthesis method (e-DIPS). Single-walled carbon nanotubes synthesized by the e-DIPS method have significantly higher purity and crystallinity, which can further improve the oxidation resistance of the support 3 in high-temperature, high-potential environments. As the support 3 of this disclosure, it is preferable to use single-walled carbon nanotubes with a G / D ratio of 70 or higher, 80 or higher, 90 or higher, 100 or higher, 110 or higher, 120 or higher, 130 or higher, 140 or higher, 150 or higher, 160 or higher, 170 or higher, 180 or higher, 190 or higher, 200 or higher, 210 or higher, or 220 or higher. The G / D ratio is measured at 1590 cm⁻¹ of the Raman spectrum of the carbon nanotube. -1 The strength of the G-band originates from the graphite structure appearing nearby, and 1350cm -1 This is the ratio of D-band intensities originating from defects appearing in the vicinity.

[0020] The support 3 may contain heteroatoms. This can further improve the conductivity in the catalyst layer. The heteroatoms contained in the support 3 may be the same type as the heteroatoms contained in the shell 4, or they may be different types.

[0021] The procedures for the first method and the second method are described as methods for producing the catalyst according to the embodiments of this disclosure.

[0022] Figure 2 is a flowchart showing the steps of a first method for producing a catalyst according to an embodiment of the present disclosure.

[0023] Carbon nanotubes are mixed with a solution containing a compound containing a heteroelement (S10). The compound containing the heteroelement may be dissolved in a solvent, or the compound containing the heteroelement may be used as the solvent. If the heteroelement is nitrogen, the compound containing the heteroelement may be urea ((NH2)2)CO. The mixed solution is filtered, and the carbon nanotubes are washed and dried (S12). The carbon nanotubes, on which the compound containing the heteroelement has adsorbed to the surface and voids, are heated to thermally decompose the compound containing the heteroelement (S14). As a result, the heteroelement contained in the compound is modified into the carbon nanotubes.

[0024] A solution for solution plasma is prepared by dissolving heteroatom-modified carbon nanotubes in a solvent (S16). Wire electrodes made of a metallic material including platinum, palladium, or an alloy containing either of these are immersed in the solution for solution plasma, and a pulse voltage is applied between the electrodes while stirring the solution with a stirrer to generate plasma in the solution (S18). Metal nanoparticles ejected from the electrodes by sputtering are supported on the carbon nanotubes. The solution is filtered through a membrane filter to create a catalyst film (S20). The film is heated and annealed (S22). As a result, the metal nanoparticles supported on the carbon nanotubes are covered with one to several layers of graphene, and the catalyst nanoparticles 2 are supported on the carbon nanotube support 3. At this time, at least a portion of the heteroatom-modified carbon nanotubes are doped into the graphene shell 4.

[0025] Figure 3 is a flowchart showing the steps of a second method for producing a catalyst according to an embodiment of the present disclosure.

[0026] A solution for solution plasma containing a compound with a heteroelement is prepared (S30). The compound with the heteroelement may be dissolved in a solvent, or the compound with the heteroelement may be used as the solvent. If the heteroelement is nitrogen, the compound with the heteroelement may be N,N-dimethylformamide (DMF, (CH3)2NCHO). A carbon electrode is immersed in the solution for solution plasma, and a pulse voltage is applied between the electrodes while stirring the solution with a stirrer to generate plasma in the solution (S32). As a result, molecules of the compound with the heteroelement generate reactive chemical species, which react with carbon atoms ejected from the carbon electrode to produce heteroelement-doped graphene. Carbon nanotubes are added to this solution (S34). As a result, the heteroelement-doped graphene is supported on the carbon nanotubes.

[0027] A precursor solution is prepared containing carbon nanotubes supported with heteroatom-doped graphene, a metal compound that will be the raw material for the metal material constituting the core 5, and a solvent (S36). If the metal material is platinum, the metal compound may be H2PtCl6 or the like. If the metal material is an alloy of platinum and cobalt, the metal compound may be H2PtCl6 and Co2(CO)8 or the like. The prepared precursor solution is reacted under high temperature or high pressure to synthesize metal nanoparticles by the solvothermal method (S38). The carbon nanotubes supported with heteroatom-doped graphene and metal nanoparticles are filtered through a membrane filter to produce a catalyst film (S40). After washing and drying the film, it is heated and annealed (S42). This removes any remaining organic solvent, and catalyst nanoparticles 2, in which metal nanoparticles are covered with one to several layers of heteroatom-doped graphene, are supported on the carbon nanotube carrier 3. The annealing treatment may be performed once or two or more times.

[0028] Figure 4 is a flowchart showing the steps of a third method for producing a catalyst according to an embodiment of the present disclosure.

[0029] A solution containing a compound with a heteroatom, a metal compound that serves as a raw material for the metal material constituting core 5, and carbon nanotubes is prepared (S50). The compound with the heteroatom may be dissolved in a solvent, or the compound with the heteroatom may be used as the solvent. If the heteroatom is nitrogen, the compound with the heteroatom may be N,N-dimethylformamide (DMF, (CH3)2NCHO). If the metal material is platinum, the metal compound may be H2PtCl6, etc. If the metal material is an alloy of platinum and cobalt, the metal compound may be H2PtCl6 and Co2(CO)8, etc. A carbon electrode is immersed in the solution for solution plasma, and a pulse voltage is applied between the electrodes while stirring the solution with a stirrer to generate plasma in the solution (S52). As a result, the synthesized metal nanoparticles, which are catalyst particles encapsulated in a heteroatom-doped graphene shell, are supported on the carbon nanotubes.

[0030] A catalyst film is prepared by filtering carbon nanotubes on which catalyst particles are supported through a membrane filter (S54). After washing and drying the film, it is heated and annealed (S56). The first annealing may be performed in a nitrogen atmosphere. The film is washed with an acid such as HClO4 (S58). The film is heated again and annealed (S60). The second annealing may be performed in an argon atmosphere containing hydrogen. To promote the formation of the L10 structure of the metal nanoparticles, it is preferable to perform the annealing treatment two or more times for at least one hour.

[0031] The film of this disclosure includes the catalyst described above.

[0032] The membrane electrode assembly of the present disclosure includes the above-mentioned membrane and an electrolyte membrane. The catalyst membrane of the present disclosure may be used as a cathode catalyst, as an anode catalyst, or as both a cathode catalyst and an anode catalyst.

[0033] [Example 1] The catalyst was prepared using the first method described above. 10 mg of single-walled carbon nanotubes (SWCNTs) and 2 g of urea were ultrasonically mixed in ethanol solvent for 15 minutes. The mixed solution was filtered, washed with ethanol, dried in an oven at 80°C, and calcined at 700°C for 1 hour under a nitrogen atmosphere. The urea decomposed and reacted with the SWCNTs to obtain nitrogen-modified SWCNTs (N-SWCNTs). 5 mg of N-SWCNTs were dissolved in 100 ml of ethanol and ultrasonically treated for 15 minutes to obtain a homogeneous mixture. Platinum electrodes were inserted into the ethanol solution, and platinum nanoparticles were synthesized by the solution plasma method. In the solution plasma method, glow discharge was performed between the platinum electrodes at 2-minute intervals per cycle, and this was repeated a total of 15 times. A DC pulse power supply with a voltage amplitude of ±5 kV, frequency of 2 kHz, and pulse width of 2.0 μs was applied between the platinum electrodes in the ethanol solution to generate plasma. It is thought that within the plasma region, ethanol molecules were excited and dissociated to form active carbon atoms or carbon clusters, which then bound to the N component on the N-SWCNTs to encapsulate the platinum nanoparticles. After solution plasma treatment, the solution was stirred overnight and filtered through a nylon membrane filter (pore size 0.45 μm). Subsequently, it was washed with acetone, methanol, and ultrapure water, and dried in an 80°C oven to obtain the precursor. Furthermore, to remove impurities from the catalyst surface, it was annealed in nitrogen at 400°C for 1 hour to prepare the catalyst of Example 1. The catalyst of Comparative Example 1 was prepared using SWCNTs instead of N-SWCNTs, following a similar procedure.

[0034] [structure] The structures of the catalysts in Example 1 and Comparative Example 1 were measured by transmission electron microscopy (TEM) and X-ray diffraction (XRD). Figure 5(a) shows the TEM image of the catalyst in Comparative Example 1. Figure 5(b) shows the TEM image of the catalyst in Example 1. When the particle size of the catalyst nanoparticles was measured in these image regions, the average particle size of the catalyst nanoparticles in Comparative Example 1 was 3.3 ± 0.9 nm, and the average particle size of the catalyst nanoparticles in Example 1 was 3.9 ± 0.9 nm. Under the same plasma generation conditions, it was observed that the average particle size of the catalyst nanoparticles in Example 1 was higher than that of the catalyst nanoparticles in Comparative Example 1. This is thought to be because the high electronegativity of the nitrogen atom increased the surface electron density of the N-SWCNTs, resulting in improved electron affinity and polar adsorption capacity. As a result, the adsorption efficiency of N-SWCNTs to platinum nanoparticles improved, and the nucleation and growth of metal particles were promoted.

[0035] As shown in Figure 5(c), in the catalyst of Example 1, mainly platinum nanoparticles coated with a single layer of graphene were observed. On the other hand, in the catalyst of Comparative Example 1, most particles did not form a carbon shell. Amorphous carbon formed by the decomposition of ethanol is difficult to precipitate on the surface of SWCNTs due to the high surface energy of SWCNTs. However, nitrogen doping lowers the surface energy of SWCNTs, and it is thought that a stable chemical bond was formed between nitrogen and amorphous carbon, resulting in the formation of nitrogen-doped carbon shells on N-SWCNTs. In SWCNTs that were not modified with nitrogen, ethanol decomposed to become activated carbon, and a graphene shell was formed on the SWCNT surface. However, in Pt / SWCNTs, only a few double-layer carbon shells were observed. This difference is thought to be because active sites were introduced on the surface of nitrogen-modified SWCNTs, making it easier to form a uniform and stable single-layer carbon shell. On the other hand, when there were no active sites on the SWCNT surface, the precipitation of carbon precursors became non-uniform, and double layers or incomplete carbon shells were formed. The amount of Pt loaded in Pt / N-SWCNTs and Pt / SWCNTs was measured by TGA and found to be 20 wt% and 23 wt, respectively.

[0036] Figure 5(d) shows the XRD patterns of a commercially available platinum-supported carbon material (Pt / C: Comparative Example 2), Comparative Example 1 (Pt / SWCNT), and Example 1 (Pt / N-SWCNT). The broad peak observed around 25° is due to the carbon support. In Comparative Example 1, XRD diffraction peaks were observed at 39.5°, 46.0°, and 67.2°, which correspond to the (111), (200), and (220) planes of metallic Pt. The average diameter of the platinum nanoparticles was calculated using Scherrer's formula. B(2θ) = Kλ / (Lcosθ) Here, K is 0.94, λ is the X-ray wavelength (copper Kα, 1.540), L is the full width at half maximum, and θ is the Bragg diffraction angle. The average diameters of the catalyst nanoparticles in Comparative Example 1 and Example 1, calculated with 2θ = 67.2°, were 8.0 nm and 8.1 nm, respectively. Compared to direct measurement by TEM imaging, the diameter measured by the XRD pattern is slightly larger, which is due to the presence of larger nanoparticles generated by unstable plasma discharge and aggregation of platinum nanoparticles during solution plasma processing. As shown in Figure 5(e), after nitrogen doping, the XRD peak of Pt(111) shifted from 39.9° to 40.1°. The corresponding (111) distance decreased from 2.29 Å to 2.22 Å, indicating a compressive strain of 3.1%. This indicates that the presence of nitrogen in Pt / N-SWCNTs results in a compressive strain effect.

[0037] Figure 5(f) shows the Raman spectra of SWCNTs, N-SWCNTs, Pt / SWCNTs, and Pt / N-SWCNTs. The ID / IG ratio of pure SWCNTs is minimal, indicating a near-defect-free state and close to 100% graphitization. Furthermore, the ID / IG ratios of N-SWCNTs, Pt / SWCNTs, and Pt / N-SWCNTs are constant, indicating that high-temperature treatment and solution plasma treatment did not destroy the structure of the SWCNTs. Therefore, it is inferred that nitrogen was added to the surface of the SWCNTs rather than within the structure.

[0038] [Chemical composition] XPS spectra were measured for the catalysts of Example 1, Comparative Example 1, and Comparative Example 2. Figures 6(a), (b), and (c) show the Pt 4f core level spectra of the catalysts of Comparative Example 1, Example 1, and Comparative Example 2. Two prominent peaks near 71.4 eV and 75.1 eV correspond to Pt 4f7 / 2 and Pt 4f5 / 2, respectively, representing metallic Pt(Pt 0 ) and ionic Pt (Pt 2+ and Pt 4+) is divided into. As shown in Figure 6(d), the ratio of metallic Pt to ionic Pt in the catalyst of Example 1 (77:23) was higher than that of Comparative Example 1 (67:33) and Comparative Example 2 (60:40), suggesting that carbon encapsulation effectively prevented oxidation of Pt. Figure 6(e) shows the XPS spectrum of N1s of the catalyst of Example 1. Two distinguishable peaks corresponding to Pt-N and graphite-N were observed at 398.7 eV and 401.5 eV. The presence of Pt-N bonds indicated a strong interaction between the platinum nanoparticles and the nitrogen-doped carbon shell. This bond stabilized the position of Pt on the support and promoted the effective deposition of the carbon source on the Pt surface during the plasma reaction. It is thought that such an interaction suppressed multilayer growth of the carbon shell and promoted the preferential formation of a single-layer structure. The XPS spectrum of C1s also detected a CN (286.8 eV) bond, suggesting that the doped nitrogen bonded with carbon to form a nitrogen-doped carbon shell. Furthermore, the modification of the SWCNT surface with nitrogen was confirmed to be consistent with the Raman spectral results. As shown in Figure 6(f), the Pt peak after nitrogen doping shifted by 0.35 eV compared to Comparative Example 1 and Comparative Example 2, indicating a shift to a higher bond energy. This shift indicates an increase in charge transfer from Pt to N-SWCNTs. Computational studies based on DFT calculations have revealed that carbon atoms adjacent to the nitrogen dopant exhibit a positive charge density because the nitrogen dopant has a strong electron affinity. It is thought that the nitrogen-doped graphene encapsulates platinum nanoparticles, and the close interaction promotes electron transfer of the platinum nanoparticles, resulting in an increase in the platinum bond energy. Platinum oxides can inhibit the adsorption of oxygen molecules and potentially reduce ORR performance, but carbon shell encapsulation and nitrogen doping can improve the durability and activity of platinum-based catalysts.

[0039] [Electrochemical Measurement] Electrochemical measurements were performed using a working electrode with a geometric area of ​​0.196 cm². 2A standard three-electrode system consisting of a glassy carbon (GC) rotating disk electrode (RDE), a platinum coil as the counter electrode, and a reversible hydrogen electrode (RHE) as the reference electrode was used for the test. The catalyst ink was prepared by dispersing 1 mg of Pt / N-SWCNT in 3 mL of IPA and 10 μL of Nafion (5%) solution. Pt / SWCNT and commercially available Pt / C inks were also prepared in the same manner. After 10 minutes of ultrasonic treatment, a uniform catalyst ink was obtained and dropped onto the GC electrode. The Pt loadings on GC for Pt / SWCNT, Pt / N-SWCNT, and commercially available Pt / C were 14.8 μg·cm -2 , 14.6 μg·cm -2 , 13.2 μg·cm -2 , respectively.

[0040] ORR performance was evaluated using cyclic voltammetry (CV) and linear sweep voltammetry (LSV) with a potentiostat / galvanostat. The electrochemical measurements were performed in 0.1 M HClO4 electrolyte at 25°C. To activate the catalyst surface, the working electrode was scanned in the range of 0.05 to 1.2 V at a scan rate of 50 mV·s under N2 saturation until steady-state voltammetry was achieved -1 . Thereafter, CV measurement of ECSA was performed at a scan rate of 50 mV·s -1 , and LSV measurement was performed under O2 saturation at a scan rate of 10 mV·s -1 and 1600 rpm (assuming the adsorption value of the hydrogen monolayer is 210 μC / cm 2 ).

[0041] Figures 7(a), (b), and (c) show the CV curves of the catalysts of Comparative Example 1, Example 1, and Comparative Example 2, respectively, in N2-saturated and O2-saturated 0.1 M HClO4. The CV curves showed hydrogen adsorption-desorption peaks and platinum formation-reduction oxidation peaks in the potential ranges of 0.05 to 0.4 V and 0.6 to 1.2 V, respectively. In the CV under O2 saturation (solid line in the figure), the ORR current increased compared to that under N2 saturation (dashed line in the figure). Assuming that 210 μC / cm is required for the oxidation of one hydrogen layer 2 , the ECSA value was calculated by integrating the charge collected in the hydrogen desorption region. Comparative Example 1 (71.0 m 2 ·g Pt-1 ) and Example 1 (65.5m 2 ·g Pt -1 ECSA in comparative example 2 (75.2m 2 ·g Pt -1 ) was slightly lower than that of Comparative Example 2. The low ECSA is due to the large size of the Pt nanoparticles, as shown in the TEM images in Figures 5(a) and 5(b). Most of the Pt nanoparticles in the catalyst of Comparative Example 1 were exposed, but the catalyst of Example 1 had more carbon shells than the catalyst of Comparative Example 1, and the reduction in the exposed Pt area due to the graphene coating is also thought to have contributed to the decrease in ECSA. The ECSA of the catalyst of Comparative Example 1 is higher than that of the catalyst of Example 1 due to the activity of the exposed Pt nanoparticles. The ORR current of the catalysts of Comparative Example 1 and Example 1 was significantly lower than that of Comparative Example 2 under N2 saturation conditions, but significantly increased under O2 saturation conditions, and in particular, the ORR current of the catalyst of Example 1 increased as the amount of graphene-encapsulated Pt nanoparticles increased. This is because the graphene shell is inactive under N2 saturation, and Pt-OH ad This weakens the formation and adsorption of Pt-OH, but suggests that oxygen reduction may occur under O2 saturation. This also suggests that the graphene shell suppresses the direct oxidation of Pt, and that oxygen reduction may be occurring on the graphene surface rather than the Pt surface. This is because, under O2 saturation conditions for the catalyst in Example 1, Pt-OH was formed at 0.8V. ad This is strongly supported by the absence of peak formation, which is clearly confirmed in the CV of comparative example 2.

[0042] Figure 7(d) shows the LSV curve when O2 is saturated at 1600 rpm. The half-wave potentials of the catalysts in Comparative Example 1, Example 1, and Comparative Example 2 were 0.850 V, 0.857 V, and 0.863 V, respectively. In the catalyst of Example 1, nitrogen doping enhanced the electronic structure of the SWCNTs, improving electrical conductivity and promoting electron transfer more efficiently. The mass activity (MA) of the catalysts in Comparative Example 1 and Example 1 at 0.9 V was 126 mA·mg pt -1 and 141mA·mg pt -1Comparative Example 2 (156mA·mg) pt -1 It was lower than ). In addition, the area specific activity (SA) of the catalysts in Comparative Example 1, Example 1, and Comparative Example 2 was 177.5 μA·cm², respectively. -2 , 215.3 μA·cm -2 , 207.4 μA·cm -2 The results were as follows. As is clear from the TEM images (Figure 5(a)(b)) and XRD spectra (Figure 5(d)(e)), the MA of the catalyst in Comparative Example 1 was lower than that of the catalyst in Comparative Example 2 due to the heterogeneous distribution of active sites and aggregation on the support. However, the MA of the catalyst in Example 1 was higher than that of the catalyst in Comparative Example 1, which suggests that the active sites were optimized by nitrogen doping, improving the area-specific activity. Furthermore, the SA of the catalyst in Example 1 was higher than that of the catalysts in Comparative Example 1 and Comparative Example 2. This increase in SA is thought to be due to the improved catalytic activity per unit area caused by the effect of nitrogen doping.

[0043] [Durability] Durability tests were conducted on the catalysts of Comparative Example 1, Example 1, and Comparative Example 2. In the single-cell test, 1 cm of film electrode assembly (MEA) was used. 2 The electrode area was used. The cathode ink was prepared by mixing and dispersing 5 mg of Pt / N-SWCNT, 5 mg of SDBS, 90 μL of Nafion (5%), and 15 mL of ethanol. To compare the performance with Pt / N-SWCNT, catalyst inks for Pt / SWCNT and commercially available Pt / C were prepared in the same manner. An appropriate amount of catalyst ink was filtered through a nylon membrane filter (pore size 0.45 μm), washed with acetone, methanol, and ultrapure water to remove excess SDBS, and then dried in an oven at 80°C for 8 hours. After drying, the film was stretched to a thickness of 1 cm. 2 It was cut into sections. The anode of the MEA was prepared in the same way as the cathode. A commercially available Pt / C was used, with a Pt load of 200 μg·cm². -2 The fabricated positive and negative electrodes were then pressed onto a Nafion film (NRE-212, thickness: 50 μm) at 140°C and 3 MPa for 3 minutes.

[0044] The assembled MEA was configured into a single fuel cell and evaluated using a fuel cell test apparatus. Carbon paper was used for the gas diffusion layer, carbon plates for the bipolar plates, and silicon for the gaskets. Prior to all MEA measurements, a constant voltage of 0.5V was applied for 2 hours at a cell temperature of 80°C (anode: H2, 1NL·min). -1 Relative humidity [RH] 81%, Cathode: Air, 2 NL·min -1 RH81%). IV measurement was performed at a cell temperature of 80°C (anode: H2, 1 NL·min). -1 RH100%, Cathode: Air, 2NL·min -1 The procedure was performed under RH100%) and repeated several times until a stable maximum current density was obtained. Before performing the CV measurement, H2(70 NmL·min) was applied to the anode. -1 ), N2 (166 NmL·min) into the cathode -1 N2 was supplied for 20 minutes to consume the O2 in the MEA. After stopping the N2 supply to the cathode, the voltage was maintained between 0.05 and 0.9V at 80°C (anode) for 50mV·s. -1 CV measurements were recorded 11 times at the scanning speed. ECSA calculations showed an adsorption value of 210 μg·cm² for the hydrogen monolayer. -2 It was assumed that: one involved applying a high-voltage triangular wave from 1V (1 sec) to 1.5V (1 sec) to accelerate the corrosion of the carrier up to 8000 cycles, and the other involved applying a rectangular voltage between 0.6V (3 sec) and 0.95V (3 sec) to the anode in an H2 atmosphere (70 NmL·min). -1 ), N2 atmosphere at cathode (166 NmL·min) -1 This simulates actual operating conditions up to 16,000 cycles.

[0045] Figures 8(a),(b), and(c) show a 5V (1 sec) high-voltage triangular wave used to accelerate carbon corrosion and simulate the harsh operating conditions of repeated start / stop cycles during long-term use. The catalyst in Example 1 showed a higher current density than the catalysts in Comparative Example 1 and Comparative Example 2 at an initial 0.6V. A sharp decrease in the current density of the catalyst in Comparative Example 2 was observed with increasing cycle count. After 8000 cycles, the current density of the catalyst in Comparative Example 2 was 406 mA·cm². -2It decreased, showing a loss of over 95%. The current density of the catalyst in comparative example 1 was 289 mA·cm². -2 The current density of the catalyst in Example 1 decreased to 305 mA·cm². -2 Although it decreased, the current density of the catalyst in Example 1 was 200 mA·cm². -2 The above was maintained. In particular, the performance of the catalyst in Comparative Example 2 deteriorated sharply after 5000 cycles, while the performance of the catalyst in Example 1 recovered slightly after 8000 cycles, demonstrating the stability of the support.

[0046] Figure 8(d) shows the change in maximum power density. As shown in Figure 8(d), after 8000 cycles, the maximum power density of the catalyst in comparative example 2 was 572.9 mW·cm². -2 From 39.1 mW·cm -2 It decreased to a significant 93.2% reduction. The maximum power density of the catalyst in comparative example 1 was 346.8 mW·cm². -2 From 242.6 mW·cm -2 It decreased to 48.3%, but the maximum power density of the catalyst in Example 1 was 463.0 mW·cm². -2 From 285.1 mW·cm -2 This resulted in a decrease of only 39.5%.

[0047] Figure 8(e) shows the maximum power density per unit of platinum load at various potential cycles. As shown in Figure 8(e), the maximum power density per unit of Pt load for the catalyst in Comparative Example 2 is 5.20 mW·cm². -2 μg pt -1 From 0.35 mW·cm -2 μg pt -1 In comparative example 1, the maximum power density per Pt-supported amount of the catalyst was 3.21 mW·cm². -2 μg pt -1 From 2.24 mW·cm -2 μg pt -1 Although it decreased, the maximum power density per Pt load of the catalyst in Example 1 was 4.63 mW·cm². -2 μg pt -1 From 2.85 mW·cm -2μg pt -1 Furthermore, the catalyst of Example 1 showed good activity and stability even when subjected to 8000 cycles of accelerated high-voltage cycling (1-1.5V).

[0048] Figure 8(f) shows the ECSA calculated from the CV curve of the MEA during the durability test. The initial ECSA of the catalysts in Comparative Example 1, Example 1, and Comparative Example 2 were 70.9 m, respectively. 2 g -1 , 60.6m 2 g -1 57.8m 2 g -1 In Comparative Example 2, the ECSA of the catalyst decreased significantly to less than 50% of its initial value after 2000 cycles, and then gradually decreased up to 8000 cycles. Similarly, the ECSA of the catalyst in Comparative Example 1 also decreased to approximately 47% of its initial value after 5000 cycles, but then gradually increased, reaching 68% of its initial value after 8000 cycles. Likewise, the ECSA of the catalyst in Example 1 decreased to approximately 63% of its initial value after 5000 cycles, but then gradually increased, reaching 67% of its initial value after 8000 cycles. This is thought to be because the recycling process removed surface impurities and oxide films, reactivating the catalyst and increasing its active area. These results demonstrate the high durability of SWCNTs as cathode catalyst supports for PEMFCs.

[0049] Durability tests were conducted using a single-cell configuration with a fuel cell test system. The potential cycle applied a rectangular potential wave of 0.6V to 0.95V with a period of 6 seconds per cycle. In the MEA test, the platinum loading amount of the catalyst in Comparative Example 1 was 100 μg·cm². -2 The catalyst stability test was conducted under rectangular potential oscillation conditions ranging from 0.6V (3 seconds) to 0.95V (3 seconds). This process simulated the potential fluctuations experienced by fuel cells during actual operation and accelerated the long-term degradation of platinum.

[0050] Figures 9(a) and 9(b) show the I-V measurement results of MEAs using the catalyst of Comparative Example 1 and the catalyst of Example 1. As shown in Figures 9(a) and 9(b), after 16000 cycles, the current density of the catalyst of Comparative Example 1 at 0.6 V is 163 mA·cm -2 decreased. However, the decrease in current density of the catalyst of Example 1 is 116 mA·cm -2 was.

[0051] Figure 9(c) shows the change in maximum power density. As shown in Figure 9(c), the maximum power density of the catalyst of Comparative Example 1 is 406 mW·cm -2 to 289 mW·cm -2 decreased, representing a decrease of 28.8%, while the maximum power density of the catalyst of Example 1 is 413 mW·cm -2 to 329 mW·cm -2 decreased, with the decrease limited to 20.3%.

[0052] Figure 9(d) shows the maximum power density per Pt loading under various potential cycles. As shown in Figure 9(d), the maximum power density per Pt loading of the catalyst of Example 1 is 4.13 mW·cm -2 μg pt -1 to 3.29 mW·cm -2 μg pt -1 decreased, while the maximum power density per Pt loading of the catalyst of Comparative Example 1 decreased from 3.78 mW·cm -2 μg pt -1 to 2.88 mW·cm -2 μg pt -1 decreased, suggesting that the catalyst of Example 1 is superior in stability and durability in the long-term cycle of 16000 cycles. For the previously reported catalyst of Comparative Example 2, after 6000 cycles at a cycle voltage of 0.6 to 0.95 V, the current density loss was already 240 mA·cm -2 , and the maximum power density of the catalyst of Comparative Example 2 was 396 mW·cm -2 to 190 mW·cm -2 decreased by 52.1%. This indicates that the catalyst of Example 1 has excellent activity and durability.

[0053] Figure 9(e) shows the ECSA calculated from the CV curve of the MEA during the durability test. As shown in Figure 9(e), the initial ECSA of the catalysts in Comparative Example 1 and Example 1 were 78.7 m, respectively. 2 g -1 , 64.7m 2 g -1 The performance of the catalyst in Comparative Example 1 was higher than that of the catalyst in Example 1 and was consistent with the ORR performance tested by RDE. This is due to the smaller particle size and greater exposure of Pt nanoparticles in the catalyst of Comparative Example 1 compared to the catalyst in Example 1. After 16,000 cycles, the ECSA of the catalyst in Comparative Example 1 decreased by 19.6%, and the ECSA of the catalyst in Example 1 decreased by 20.2%, indicating that minimal loss persisted. These results suggest that SWCNTs exhibit high durability and activity as a support material for PEMFC cathode catalysts.

[0054] Figures 10(a) and 10(b) show the changes in particle size of the catalysts in Comparative Example 1 and Example 1 after 8000 cycles of potential cycling between 1 and 1.5 V. As shown in Figure 10(a), the average particle size of the catalyst in Comparative Example 1 increased from 3.3±0.9 nm to 3.5±0.8 nm, indicating that catalyst aggregation occurred. As shown in Figure 10(b), the average particle size of the catalyst in Example 1 increased from 3.9±0.9 nm to 4.1±0.8 nm, indicating that it mainly maintained the nanoparticle morphology. The increase in particle size is thought to be due to the accumulation of dissolved Pt metal in Pt nanoparticles without carbon shells.

[0055] Figures 10(c) and 10(d) show the changes in particle size of the catalysts in Comparative Example 1 and Example 1 after 16,000 cycles of potential cycling between 0.6 and 0.95 V. As shown in Figure 10(c), the average particle size of the catalyst in Comparative Example 1 increased from 3.3 ± 0.9 nm to 3.5 ± 0.9 nm, maintaining the nanoparticle morphology. As shown in Figure 10(d), the average particle size of the catalyst in Example 1 increased from 3.9 ± 0.9 nm to 4.0 ± 0.9 nm, showing almost no change. This result indicates that the carbon shell remained relatively stable during the 0.6 to 0.95 V cycle, effectively preventing nanoparticle aggregation and maintaining catalyst stability.

[0056] Figures 10(e) and 10(f) show the Pt 4f XPS spectra of the catalyst in Comparative Example 1 and Example 1 after the initial state before the durability test and after potential cycling at 8000 (1.0-1.5V) and 16000 (0.6-0.95V), respectively. As shown in Figure 10(e), under the harsh durability test conditions, the Pt nanoparticles showed a shift to the high-energy band, which is thought to be due to the oxidation of some Pt ​​atoms. As shown in Figure 10(f), the Pt peak of the catalyst in Example 1 remained unchanged after the durability test, maintaining the reduced state. This stability under harsh conditions demonstrates the high performance and durability of the catalyst in Example 1.

[0057] Figures 11(a) and 11(b) show the Raman spectra of Comparative Example 1 and the catalyst of Example 1 after the durability test. As shown in Figure 11(a), the D band was significantly increased after 8,000 cycles at a high potential of 1.0–1.5 V compared to after 16,000 cycles at a potential of 0.6–0.95 V, suggesting that high-potential cycling accelerated the oxidation of Pt / SWCNTs, leading to an increase in carbon defects on the SWCNT surface. A similar phenomenon was observed in Pt / N-SWCNTs, as shown in Figure 11(b).

[0058] Figures 12(a) and 12(b) show the XPS spectra of N1s in Comparative Example 1 and the catalyst of Example 1 after the durability test. As shown in Figures 12(a) and 12(b), the XPS subpeaks of N1s after the durability test are consistent with those before the durability test, indicating that graphite-N is relatively stable and no transformation has occurred. However, the proportion of graphite-N has decreased compared to Pt-N. This is thought to be due to the partial decomposition of the carbon shell during the long potential cycle.

[0059] Generally, the main causes of performance degradation in PEMFCs after long-term operation are considered to be the increased oxidation state of Pt, dissolution / regeneration, corrosion of the carbon support, and a decrease in the active surface area of ​​Pt after poisoning (58). 58 Therefore, it was shown that encapsulating nitrogen-doped graphene on Pt / N-SWCNT effectively prevents a decrease in catalytic activity due to the adsorption of impurities to the catalyst surface, and further suppresses direct oxidation of the platinum surface, thereby effectively suppressing catalyst degradation at high temperatures. These results suggest that nitrogen-doped graphene-encapsulated platinum catalysts are promising candidates to address the current challenge of long-term durability of PEMFC cathode catalysts.

[0060] [Example 2] The catalyst was prepared using the second method described above. A pair of carbon electrodes were inserted into a glass reactor, with the tips of the electrodes positioned 1.0 mm apart in the center of the reactor. Both electrodes, immersed in 100 ml of DMF, were connected to a bipolar pulse power supply. The plasma operating conditions were fixed at a pulse width of 1.5 μs, voltage of 2 kV, and frequency of 20 kHz for 40 minutes. 10 mg of e-DIPS SWCNTs were added to the solution after solution plasma treatment and stirred overnight with ultrasound. The SWCNTs were collected on a nylon membrane filter, washed several times with acetone, methanol, and pure water, and then dried at 80°C for 5 hours. Next, the dried SWCNTs were added to a Pt precursor solution prepared by mixing H2PtCl6 solution (8 wt%, 100 mg), DMF (12 mL), and ethylene glycol (8 mL), and stirred overnight. A mixture dispersed by ultrasound for 15 minutes was reacted in a Teflon-lined autoclave at 170°C for 8 hours to synthesize platinum nanoparticles. After cooling to room temperature, the reaction product was collected on a nylon membrane filter, washed several times sequentially with acetone, methanol, and pure water, and then dried overnight at 80°C. Subsequently, the recovered catalyst was annealed in a mixed gas at 220°C for 1 hour to obtain a nitrogen-doped, multi-layer graphene shell-encapsulated platinum nanocatalyst (N-FLG@Pt / SWCNT) supported on SWCNTs.

[0061] [structure] The structure of the catalyst in Example 2 was measured by transmission electron microscopy (TEM) and X-ray diffraction (XRD). Figures 13(a) and 13(b) show the TEM images of the catalyst in Example 2. It can be confirmed that all platinum nanoparticles are encapsulated in nitrogen-doped graphene. Figure 13(c) shows the particle size distribution of the catalyst in Example 2. The average diameter of the catalyst in Example 2 was 3.30 nm. Figure 13(d) shows the XRD patterns of the catalyst in Example 2 before and after heat treatment. The diffraction peaks associated with Pt(111), Pt(200), and Pt(220) of the catalyst in Example 2 after heat treatment were located at 40.16°, 46.50°, and 67.88°, respectively, showing characteristic reflections of face-centered cubic Pt crystals (JCPDS, No. 04-0802). Doping with nitrogen atoms induces electron transfer of Pt, slightly changing the lattice constant of Pt and shifting the diffraction peaks to higher angles. This change in the Pt diffraction peak has been observed in other reports as well.

[0062] [Electrochemical Measurement] The catalyst ink for electrochemical testing was prepared by mixing 0.6 mg of the catalyst from Example 2 with 1 mL of ethanol and 45 μL of Nafion solution (5 wt%), and sonicating for 10 minutes. 45 μl of the prepared ink was dropped onto a glassy carbon (GC) rotating disk electrode (5.5 mm in diameter) and dried by spin-assisted drying (700 rpm). A commercially available Pt / C was prepared similarly (Comparative Example 2). A Pt wire was used as the counter electrode, and an Ag / AgCl (saturated KCl) electrode was used as the reference electrode. Cyclic voltammetry (CV) and linear scanning voltammetry (LSV) were used to evaluate the catalyst. Measurements were performed using a standard three-electrode system with a potentiostat / galvanostat. The Pt loading amount in GC for Example 2 and Comparative Example 2 was 9.09 μg / cm³, respectively. 2 , 14.6 μg / cm³ 2 All electrochemical measurements were performed at room temperature in a 0.1 M HClO4 electrolyte. Cyclic voltammetry measurements were performed in a N2-saturated 0.1 M HClO4 solution at a potential scan rate of 50 mV / s between 0.05 and 1.2 V (51 cycles). The electrochemically active surface area (ECSA) was 210 μC / cm². 2Assuming this, the measurement was performed by integrating the hydrogen underpotential deposition (Hupd) peak in cyclic voltammetry. LSV measurements were performed under O2 saturation, with a potential scan rate of 10 mV / s and a rotating disk speed of 1600 rpm.

[0063] Figure 14(a) shows the ORR polarization curves of Comparative Example 2 and the catalyst of Example 2. The half-wave potential (E1 / 2) (0.861V) of the catalyst of Example 2 is higher than that of the catalyst of Comparative Example 2, indicating the enhancement of the ORR process by N-doped graphene. Figures 14(b) and (c) show the CV curves of Comparative Example 2 and the catalyst of Example 2. ECSA was calculated from the CV curve by integrating the charge collected in the hydrogen desorption region. The ECSA of the catalysts of Comparative Example 2 and Example 2 are 60.6 m, respectively. 2 / g, 94.76m 2 The values ​​were / g. When platinum is encapsulated in graphene, the exposed area of ​​platinum decreases, and the ECSA decreases. However, nitrogen-doped graphene has excellent proton permeability, oxygen transportability, adsorption capacity, and reducing capacity, so the entire surface of nitrogen-doped graphene and platinum nanoparticles can be fully involved in the catalytic reaction. The mass activity (MA) and specific activity (SA) of the catalyst in Example 2 at 0.9V were 305.49 mA / mg and 326.37 μA·cm². -2 Both are commercially available Pt / C (174 mA / mg and 186.21 μA·cm). -2 ) was significantly higher.

[0064] [Durability] A membrane electrolyte assembly (MEA) was installed for single-cell testing (electrode area 1 cm²). 2To prepare a homogeneous catalyst ink for the cathode, 6 mg of N-Gns@Pt / SWCNT, 96 μL of Nafion 5%, 15 mL of ethanol, and 6 mg of SDBS were mixed and then sonicated for 15 minutes. The N-Gns@Pt / SWCNT catalyst ink was collected by filtration through a nylon (pore size 0.45 μm) membrane filter, washed several times sequentially with acetone, methanol, and pure water to remove SDBS, and then dried overnight at 80°C. The Pt load on the membrane filter coated with the N-Gns@Pt / SWCNT catalyst was 0.053 mg / cm³. 2 The anode was prepared by mixing 75 mg of Pt / C, 200 mg of Nafion 20%, 540 mg of 2-propanol, and 420 mg of ultrapure water. This anode catalyst ink was dropped onto a Teflon® film and rubbed into the film using a smart table coater. The amount of Pt loaded onto the Teflon film coated with the Pt / C catalyst was 0.2 mg / cm². 2 The prepared cathode and anode were pressed onto a Nafion NRE-211 film (25 μm thick) at 140°C and 1.5 MPa for 3 minutes. For comparison, a reference MEA was prepared using the same method with Pt / C as the cathode catalyst layer.

[0065] Prepared MEA 1 cm 2The fuel cell was loaded into a single fuel cell, and its performance was evaluated using a fuel cell test apparatus. The MEA was initially activated by scanning an H2 / airflow (0.07 / 0.166 L / min) between 0.2 and 0.8 V under conditions of 80°C, 0 kPaabs, and 100% relative humidity (RH). IV measurements were performed using an H2 / airflow (1 / 2 L / min) under conditions of 80°C, 0 kPaabs, and 100% RH. CV measurements were performed by scanning between 0.05 and 0.9 V at a scan speed of 50 mV / s 10 times under conditions of H2 / N2 flow (0.07 / 0 L / min), 80°C, 0 kPaabs, and 100% RH. To evaluate the long-term durability of the N-Gns@Pt / SWCNT catalyst, an ADT (Adaptive Decompression Test) was performed for 60,000 cycles under conditions of 80°C, 0 kPaabs, and 100% RH, using an H2 / N2 flow (0.07 / 0.166 L / min), 0.6 V, 3 seconds, and a square wave at 0.95 V, 3 seconds. Furthermore, under conditions of 80°C, 0 kPaabs, and 100% RH, a start-stop test was performed using an H2 / N2 flow (0.07 / 0.166 L / min) at voltages ranging from 1.0 V to 1.5 V, with each cycle lasting 2 seconds, to evaluate the corrosion of the carbon support. IV and CV measurements were performed at several locations during the two durability tests.

[0066] Figures 15(a) and (b) show the ultra-low Pt load (0.053 mg / cm³) recorded during the ADT trial. 2 Figures 15(c) and 15(d) show the IV and CV curves of the MEA (0.2 mg / cm³) when the catalyst of Comparative Example 2 was used as the cathode. 2 The IV and CV curves are shown, respectively. For fairness, the amount of platinum loading in the cathode should be the same for all MEA materials, but it is difficult to fabricate MEAs with ultra-low cathode Pt loading using commercially available Pt / C. Commercial Pt / C has a high Pt ratio, and the amount of Pt loading in the MEA cathode is extremely low, so fabricating an extremely thin cathode under these constraints may have a significant negative impact on the MEA test results. Therefore, the amount of Pt loading in the cathode is set to 0.2 mg / cm³. 2 A commercially available Pt / C-based MEA was used as the reference. The anode Pt load was the same for all MEAs: 0.2 mg / cm³.2 Figure 15(e) shows the ECSA calculated from the CV curves of the MEA using N-Gns@Pt / SWCNT and commercially available Pt / C recorded during ADT. For N-Gns@Pt / SWCNT, the initial ECSA was 95.31m. 2 The retention rate after 30,000 cycles was 89.88% for Pt / g, compared to 66.89m for commercially available Pt / C (each 66.89m). 2 The percentage significantly exceeded 45.73% ( / g). Furthermore, after 60,000 cycles, N-Gns@Pt / SWCNT was 81.65% (77.82m). 2 An astonishing ECSA retention rate of 1 / g was achieved. This strongly indicates that nitrogen-doped graphene accelerates the ORR process and possesses extremely high durability, representing the highest level of ECSA and ECSA retention reported in MEA studies to date.

[0067] Figures 16(a) and (b) show the maximum power density at 0.8V and the change in power density with the number of ADT cycles for the catalysts of Example 2 and Comparative Example 2. Figures 16(c) and (d) show the maximum power density per Pt load at 0.8V and the change in power density with the number of ADT cycles for the catalysts of Example 2 and Comparative Example 2. The initial maximum power density of the catalyst in Example 2 was 419 mW / cm². 2 And commercially available Pt / C (863mW / cm²) 2 Although it was lower than ), this was due to the extremely low amount of Pt supported in the cathode layer and the difficulty in dispersing the SWCNTs. The power density per gram of Pt better represents the catalytic activity of the catalyst in Example 2. Initial maximum power density per amount of Pt supported (7.91 mW·cm²) -2 μg Pt -1 ) is a commercially available Pt / C (4.32 mW·cm²). -2 μg Pt -1This is 1.83 times that of the previous example, demonstrating high efficiency. However, the power density retention trend of the catalyst in Example 2 after 30,000 and 60,000 cycles (69.46% and 57.28%, respectively) was similar to that of commercially available Pt / C (72.30% and 59.33%, respectively). A similar trend was observed in the change in power density at 0.6V. Under practical operating conditions for single-cell PEMFCs, the maximum power density is usually located within the ohmic polarization zone, where the resistance to ion flow within the proton exchange membrane (Nafion) and the electronic resistance of the external circuitry dominate current loss. The power density change within the activated polarization zone is likely to be more representative in comparing the durability of nanoparticles. In the low-current zone, electrochemical reaction kinetics dominate current loss, which is directly reflected in the power density at low currents. Therefore, when comparing the power density at 0.8V and the power density per Pt load of the catalyst in Example 2 and the comparative example 2 catalyst according to the number of ADT cycles, the power density retention rates of the catalyst in Example 2 after 30,000 cycles and 60,000 cycles at 0.8V (80.81% and 61.92%, respectively) were significantly higher than those of the comparative example 2 catalyst (23.26% and 12.79%, respectively). This maintenance of power density demonstrates the outstanding durability of the catalyst in Example 2 under ultra-low Pt load conditions.

[0068] To demonstrate the extremely high oxidation resistance of SWCNTs, an AST test was performed for 30,000 cycles by applying a high-voltage triangular wave of 1.0V to 1.5V with a period of 2s per cycle. Figures 17(a) and 17(b) show the ultra-low Pt load (0.053 mg / cm³) recorded during the AST test. 2 Figure 17(c)(d) shows the IV and CV curves of the MEA when the catalyst of Example 2 was used as the cathode. 2The IV and CV curves are shown. After 30,000 cycles, the catalyst of Example 2 showed a significantly higher ECSA retention rate of 52.89% than the catalyst of Comparative Example 2 (29.09%). The maximum power density of the catalyst of Comparative Example 2 decreased significantly to approximately 23.90% of the initial value at 5,000 cycles, and then gradually decreased to 8.53% by 30,000 cycles. In contrast, the power density of the catalyst of Example 2 decreased only to 78% at 5,000 cycles, and then gradually decreased to 39.64% by 30,000 cycles. Notably, the change in power density at various voltages shows a consistent, gradual, and stable decrease rather than a sharp decay. This clearly demonstrates that the extremely high oxidation resistance of SWCNTs significantly extends the life of the MEA compared to conventional carbon materials.

[0069] To understand the high performance and durability of the catalyst in Example 2, the state of Pt nanoparticles and SWCNTs before and after durability testing was further evaluated. Figures 18(a), (b), and (c) show the Pt 4f core level spectra of the catalyst in Example 2 before ADT testing, after 60,000 ADT cycles, and after 30,000 AST cycles, respectively. The characteristic peaks of Pt 4f7 / 2 and Pt 4f5 / 2 at 71.4 eV and 75.1 eV are Pt 0 and Pt 2+ It can be separated into. Figure 18(d) shows the Pt 4f spectrum after deconvolution. 0 and Pt 2+ The peak area ratio is shown, and the catalyst of Example 2 has an excellent relative ratio of metallic Pt to ionic Pt (Pt 0 :Pt 2+ The ratio (84.83:15.17) significantly surpasses that of the catalyst in Comparative Example 2, demonstrating the superior oxidation resistance of nitrogen-doped graphene. Another trend observed was a slight decrease in the ratio of metallic Pt to ionic Pt in the catalyst of Example 2, to 71.89:28.11 after 60,000 cycles of ADT and to 79.55:20.45 after 30,000 cycles of AST. This result indicates that nitrogen-doped graphene has a very strong inhibitory effect on Pt-O bond formation.

[0070] Raman spectroscopy was performed to confirm the change in the degree of defects in SWCNTs during durability testing. Figures 19(a) and 19(b) show the Raman spectra of SWCNTs, the catalyst of Example 2, the catalyst of Example 2 after ADT testing, and the catalyst of Example 2 after AST testing. The D peak of Pt / SWCNT increased slightly due to oxidation, but the degree of crystallinity remained unchanged. This indicates that SWCNTs are promising as a support material for PEMFC electrode catalysts.

[0071] Figures 20(a),(b), and(c) show TEM images of the catalyst in Example 2 and histograms of Pt nanoparticles after 60,000 cycles of ADT. Figures 20(d),(e), and(f) show TEM images of the catalyst in Example 2 and histograms of Pt nanoparticles after 30,000 cycles of AST. After the ADT test, no core-shell structure was observed in the catalyst in Example 2, suggesting that the nitrogen-doped graphene gradually dissolved during the test. Under the harsh high-voltage triangular wave of AST, the catalyst in Example 2 showed significant aggregation, but no larger nanoparticles were formed. Furthermore, different nanowire structures were observed in the catalyst in Example 2 after the durability test. After the ADT test, individual Pt nanoparticles aligned into elongated nanowires of varying lengths along the direction of the N-Gns@Pt / SWCNT bundle. After the AST test, the Pt nanoparticles aggregated along the same direction, forming one-dimensional nanoclusters. Such unique structural changes are rarely seen after durability testing in conventional electrocatalysts using carbon materials. The one-dimensional arrangement of SWCNTs is thought to restrict the movement of platinum nanoparticles, thereby improving durability at a physical level. This finding provides a new direction for the design of PEMFC electrode catalysts.

[0072] [Example 3] The catalyst was prepared using the third method described above. SWCNTs (10 mg), H2PtCl6.6H2O (50 mg), and Co2(CO)8 (35 mg) were dispersed in DMF, sonicated for 15 minutes, and then stirred overnight. The prepared solution was poured into a glass reactor. A pair of carbon rods were placed in the glass reactor at a distance of 1 mm, and both carbon electrodes were connected to a bipolar pulse power supply. Solution plasma synthesis was performed for a total of 30 minutes at a frequency of 30 kHz and a pulse width of 1.5 μs. Details of the applied voltage are shown in Figure 21. After the solution plasma synthesis was completed, the solution was stirred overnight. The reaction products were collected on a nylon membrane filter, washed several times sequentially with acetone, methanol, and pure water, and then dried overnight at 80°C to remove residual solvent. The sample was annealed twice sequentially in an electric furnace. The first annealing was performed at 800°C for 3 hours in a nitrogen atmosphere (0.26 L / min) to obtain carbon-encapsulated PtCo alloy nanoparticles. Before the second annealing, the annealed samples were washed with 0.1 M HClO4 at 60°C for 30 minutes to remove non-alloy cobalt nanoparticles. The second annealing was performed at 700°C for varying times in a 5% hydrogen + argon atmosphere to promote the formation of L10 structured PtCo alloy nanoparticles. After the second annealing, the L10-PtCo / c / SWCNTs were characterized.

[0073] [structure] Figure 22 shows the XRD patterns of the catalyst from Example 3 annealed in a 5% hydrogen-argon gas mixture for 1 hour (top), 3 hours (middle), and 5 hours (bottom). Clear PtCo peaks corresponding to the (111), (200), (201), and (202) lattice planes were observed. In particular, the PtCo(111) peak appeared around 41.4° in all samples, indicating the presence of an L10 structure with a Pt:Co atomic ratio of 1:1. This suggests that annealing in a 5% hydrogen-argon atmosphere promotes the formation of the L10 phase. However, as the annealing time increased, the crystal size increased, as can be seen from the sharpening of the diffraction peaks. As a result, in the sample annealed for 5 hours, the PtCo(110) peak at 33.3°, characteristic of the L10 structure, became clear. The crystal size estimated from the Pt(111) peak reached 5.9 nm after 5 hours of annealing.

[0074] Figure 23 shows a TEM image of the catalyst from Example 3. The TEM image revealed PtCo / c / SWCNT alloy nanoparticles encapsulated within a carbon shell. The nanoparticles showed a bimodal particle size distribution, with larger particles having a diameter of approximately 10 nm and smaller particles having a diameter of approximately 3 nm.

[0075] Figure 24 shows the energy-dispersive spectroscopy (EDS) image of the catalyst from Example 3. The EDS image confirmed that the synthesized nanoparticles are a platinum-cobalt bimetallic alloy. Quantitative analysis of the EDS mapping showed that the Pt:Co atomic ratio was close to 1:1, which is consistent with the results obtained from XRD analysis.

[0076] [Electrochemical Measurement] A standard three-electrode system with a potentiostat / galvanostat was used for electrochemical measurements. The ORR performance of the synthesized catalyst was evaluated in 0.1 M HClO4 electrolyte at 25°C. The working electrode was a glassy carbon (GC) rotating disk electrode (RDE, geometric area: 0.1256 cm²). 2 A platinum coil was used as the counter electrode, and a reversible hydrogen electrode (RHE) was used as the reference electrode. Cyclic voltammetry (CV) was performed at 50 mV·s between 0.05 and 1.2 V under N2 saturation. -1 The scan rate was 0.05–1.1V, and the electrochemical surface area (ECSA) was calculated by integrating the H-desorption charge. LSV measurements were performed at 0.05–1.1V and a scan rate of 10mV·s. -1 The test was performed at a rotation speed of 1600 rpm under O2 saturation. The catalyst ink for the electrochemical test was prepared by mixing the catalyst from Example 3 (0.6 mg) with 1 mL of ethanol and 45 μL of Nafion solution (5 wt%), and sonicating for 10 minutes. 45 μl of the prepared ink was dropped onto the glassy carbon (GC) of a rotating disk electrode and dried by spin-assisted drying (700 rpm). The amount of Pt supported on the catalyst on the GC was 7.31 μg / cm³. 2 That was the case.

[0077] Figure 25 shows the CV curve of the catalyst in Example 3. Figure 26 shows the LSV curve of the catalyst in Example 3. Figure 27 shows the platinum loading, ECSA, MA, and SA of the catalyst in Example 3. Electrochemical measurements using CV and LSV revealed that increasing the annealing time in a 5% hydrogen-argon atmosphere increased both the ECSA and mass activity (MA) of the synthesized sample. While prolonged annealing increased the size of the PtCo / c / SWCNT alloy nanoparticles, it also promoted the formation of the L10 structure. These results indicate that the L10 structure significantly improves electrochemical catalytic activity, even though direct contact between the PtCo alloy catalyst and the reactants is limited by carbon encapsulation.

[0078] The present disclosure has been explained above based on examples. These examples are illustrative, and it will be understood by those skilled in the art that various modifications are possible in combinations of their components and processing processes, and that such modifications are also within the scope of the present disclosure. [Explanation of Symbols]

[0079] 1... Catalyst, 2... Catalyst nanoparticles, 3... Support, 4... Shell, 5... Core, 6... Void.

Claims

1. Catalyst particles comprising a shell containing a carbon material and a core containing a metal material enclosed within the shell, A carrier supporting the catalyst particles, Equipped with, The aforementioned shell contains amorphous carbon doped with heteroatoms, The carrier contains carbon nanotubes. catalyst.

2. The carrier includes single-walled carbon nanotubes. The catalyst according to claim 1.

3. The amorphous carbon includes graphene. The catalyst according to claim 1.

4. The carrier contains heteroatoms The catalyst according to claim 1.

5. The heteroatom is nitrogen. The catalyst according to any one of claims 1 to 4.

6. The steps include preparing a mixed solution containing a compound with heteroatoms and carbon nanotubes, A step of heating carbon nanotubes extracted from a mixed solution to thermally decompose the compound, thereby incorporating heteroatoms into the carbon nanotubes, A step of generating plasma by applying a voltage from an electrode containing a metallic material in a solution containing carbon nanotubes containing heteroatoms, The process involves supporting catalyst particles, which are metal material particles synthesized by solution plasma and coated with heteroatom-doped amorphous carbon, onto carbon nanotubes. A method for producing a catalyst containing [the specified ingredient].

7. A step of generating plasma in a solution containing a compound containing heteroatoms, The process involves adding carbon nanotubes to a solution to support heteroatom-doped amorphous carbon onto the carbon nanotubes, The process involves heating a solution containing carbon nanotubes supported with heteroatom-doped amorphous carbon and a metal material to support catalyst particles, in which particles of the metal material are coated with heteroatom-doped amorphous carbon, onto the carbon nanotubes. A method for producing a catalyst containing [the specified ingredient].

8. The steps include preparing a solution containing a compound with heteroatoms, a metal compound containing a metal material, and carbon nanotubes, The steps include generating plasma in the aforementioned solution, The steps include: heating the carbon nanotubes removed from the aforementioned solution, The process involves supporting catalyst particles, which are metal material particles synthesized by solution plasma and coated with heteroatom-doped amorphous carbon, onto carbon nanotubes. A method for producing a catalyst containing [the specified ingredient].

9. Carbon nanotubes are synthesized using the enhanced Direct Injection Pyrolytic Synthesis method (e-DIPS). The method according to any one of claims 6 to 8.

10. A film comprising the catalyst according to any one of claims 1 to 4.

11. The film according to claim 10, Electrolyte membrane, A membrane electrode assembly comprising the above components.